Development of temperature regime of storage of frozen black curran - Osokina, Nina; Kostetska, Kateryna; Herasymchuk, Olena; Tkachenko, Hennadii; Podpriatov, Hryhorii; Pusik, Ludmila; Falendysh, Natalia; Bobel (Zinchenko), Inna; Belinska, Kristina (My University, 2021)
The process of ice formation in the pericarp of black currant depends on the pomological variety, the degree of ripeness of the fruit, and the method of freezing. It is scientifically substantiated that the temperatures of freezing fruits significantly change the general existing recommendations (not higher than –18 °С) regarding the storage conditions of black currant fruits: with quick freezing, not higher than –21 °С, with slow freezing, not higher than –24 °С. The formation of the properties of black currant occurs during the growing season under various agro-climatic conditions and affects the parameters of ice formation indicators. The marketable condition, quality and organoleptic characteristics of black currant fruits depend on the method of freezing. The advantages of fast freezing of black currant fruits in a quick-freezing chamber with forced air circulation at a speed of 1.5–2.5 m/s at a temperature of –30...–32 °С. Процес льодоутворення в перикарпію чорної смородини залежить від помологічного сорту, ступеня стиглості плодів та способу заморожування. Науково обґрунтовано, що температури заморожування плодів суттєво змінюють загальні існуючі рекомендації (не вище -18 °С) щодо умов зберігання плодів чорної смородини: при швидкому заморожуванні — не вище -21 °С, при повільному заморожуванні — не вище -24 °С. Формування властивостей плодів чорної смородини відбувається протягом вегетаційного періоду в різних агрокліматичних умовах і впливає на параметри показників льодоутворення. Товарний вигляд, якість та органолептичні показники плодів чорної смородини залежать від способу заморожування. Встановлено переваги швидкого заморожування плодів чорної смородини в камері швидкого заморожування з примусовою циркуляцією повітря зі швидкістю 1,5-2,5 м/с за температури —30...-32 °С.
Keywords: black currant fruit; cooling; freezing; ice formation; fruit quality; плоди чорної смородини; охолодження; заморожування; льодоутворення; якість плодів; кафедра технології хлібопекарських і кондитерських виробів